Chapter 16 Socio-Demographic Determinants Of Risky Sexual Behavior Among Adolescents: A Case Study Of Homa-Bay County, Ken - Muhonja, Faith; keraka, Margaret; Ndayala, Phoebe (CEDRED Publications, 2022)
Abstract Over the past decade, prevalence of risky sexual behavior among adolescent 15-19 years has been on upward trajectory. Globally, more than a half of adolescents engage in risky sexual behaviour. Sub-Saharan region has highest early sexual debut (46.3%). There is low (41.2%) condom use while prevalence of multiple sexual partners is 44.5%. In Homa-Bay County, more than 60% of adolescents engage in risky sexual behaviour; approximately 60% of adolescent males have their sexual debut before 15 years which is thrice the national prevalence of (21%). Studies have shown risky sexual behavior to be more prevalence among the low and middle income countries with more girls engaging in risky sexual behavior compared to their male counterparts. This study endeavored to assess determinants of risky sexual behavior among adolescents in Homa-Bay County, Kenya. The study used descriptive study design. A sample size of 306 participants were interviewed by use of interviewer led questionnaire. Key informant interview guide was used to collect qualitative data from 12 key informants. Data analysis tools were MS-Excel and Stata V 14 and thematic content analysis. Findings indicated other than sex (O.R.=2.016; C.I.=0.23-1.16; P=0.008) and age (O.R.=1.033; C.I.=0.61-3.32; P=0.043) other factors showed no significant association (P>0.05) with risky sexual behavior. Age was positively correlated with indulgence in risky sexual behavior among adolescents 15-19 years. Males were twice more likely to engage in risky sexual behavior compared to their female counterparts. The study concluded that age and sex as determinants of adolescents’ risky sexual behavior.
Keywords: Adolescents; risky sexual behaviour; social determinants